The use of nest-boxes by two species of sparrows ("Passer domesticus" and "P. montanus") with opposite trends of abundance - the study in Warsaw - Węgrzynowicz, Andrzej (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The occupation of nest-boxes by House- and Tree Sparrow in Warsaw was investigated in 2005-2009 and in 2012. Riparian forests, younger and older parks in downtown, and housing estates were included in the study as 4 types of habitats corresponding to the urbanization gradient of Warsaw. 1035 inspections of nest-boxes suitable for both species (type A) were carried out during the breeding period and 345 nest-boxes of other types were inspected after the breeding period.
Keywords: House Sparrows; Tree Sparrow; nest sites; nest-boxes; decrease in Sparrows number; competition; Warsaw